2015
DOI: 10.1111/fog.12126
|View full text |Cite
|
Sign up to set email alerts
|

Coupling an oceanographic model to a Fishery Observing System through mixed models: the importance of fronts for anchovy in the Adriatic Sea

Abstract: Anchovy, Engraulis encrasicolus, forms the basis of Italian small pelagic fisheries in the Adriatic Sea. The strong dependence of this stock on environmental factors and the consequent high variability makes the dynamics of this species particularly complicated to model. Weekly geo-referenced catch data of anchovy obtained by means of a Fishery Observing System (FOS) from 2005 to 2011 were referred to a 0.2 9 0.2 degree grid (about 20 km 2 ) and associated with the environmental parameters calculated by a Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…As a consequence, more local drivers had to be investigated in order to better understand these fluctuations. For example, anchovy optimal habitat is usually seen to be related to high frontal activities and areas with river inputs (Agostini and Bakun, 2002;Morais et al, 2012;Giannoulaki et al, 2013;Carpi et al, 2015), resulting in strong water masses mixing. The covariation between anchovy body condition and Eke observed in the PCA thus tended to confirmed that important mesoscale activity might create favorable biotic conditions for this species, which .…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, more local drivers had to be investigated in order to better understand these fluctuations. For example, anchovy optimal habitat is usually seen to be related to high frontal activities and areas with river inputs (Agostini and Bakun, 2002;Morais et al, 2012;Giannoulaki et al, 2013;Carpi et al, 2015), resulting in strong water masses mixing. The covariation between anchovy body condition and Eke observed in the PCA thus tended to confirmed that important mesoscale activity might create favorable biotic conditions for this species, which .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the geo-and time-referenced abundance indexes (CPUE) obtained via this kind of monitoring system can be compared with the in situ measurements simultaneously collected and other detailed sets of environmental descriptors in order to achieve a general understanding about the effects of environmental drivers on the abundance and distribution of fish stocks (e.g. to explain how the environment can affect recruitment success and fish migration; see Falco et al 2007Falco et al , 2011Carpi et al 2015). The integration of catch and oceanographic data is fundamental for understanding the processes regulating fish stock distribution during the various phases of the life cycle; this information is necessary in order to regulate sustainable fishery development (Martinelli et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The stock assessment, historically carried out using a single species VPA-type model, in the last decade has undergone significant changes: the methodology moved to a more sophisticated statistical catch at age model (SAM), and the whole dataset has been entirely revised to improve the quality of the results and provide more accurate scientific advice (GFCM, 2014(GFCM, , 2015. However, the biggest improvement lies in the fact that these stocks have been the guinea pig for a series of processes that are meant to become common practice in the region, following the ICES example: their stock assessment was subjected to a benchmark process (GFCM, 2015), the EU prepared a multiannual management plan for the management of these stocks that has been adopted with recommendation GFCM/37/2013/1 of the General Fisheries Commission for the Mediterranean (GFCM), and a Management FIGURE 2 | Haul tracks of Italian pelagic trawlers and purse seiners (gray and purple tracks) monitored through a Fishery Observing System (Carpi et al, 2014). The maps represent 5 years of data for eight vessels belonging to the main Italian ports targeting small pelagics.…”
Section: Small Pelagics: Anchovy and Sardinementioning
confidence: 99%